Coping with COVID-19. Work life experiences of nursing, midwifery and paramedic academics: An international interview study. (December 2022) - Brown, Janie; Slatyer, Susan; Jakimowicz, Samantha; Maben, Jill; Calleja, Pauline; Donovan, Helen; Cusack, Lynette; Cameron, Dawn; Cope, Vicki; Levett-Jones, Tracy; Williamson, Moira; Klockner, Karen; et al.
Abstract: Background: The COVID-19 global pandemic was declared in March 2020. By June 2022, the total deaths worldwide attributed to COVID-19 numbered over 6.3 million. Health professionals have been significantly impacted worldwide primarily those working on the frontline but also those working in other areas including nursing, midwifery, and paramedic higher education. Studies of occupational stress have focused on the clinical health professional roles but scant attention has been drawn to the pressures on university-based academic staff supporting and preparing professionals for frontline health work. Design and objectives: This qualitative study sought to explore the challenges experienced by health academics (nurses, midwives and paramedics), during COVID-19 and identify strategies enlisted. Setting and participants: Six Australian and two United Kingdom universities collaborated, from which 34 health academics were individually interviewed via video or teleconference, using six broad questions. Ethical approval was obtained from the lead site and each participating University. Data analysis: Thematic analysis of the data was employed collaboratively across institutions, using Braun and Clarke's method. Results: Data analysis generated four major themes describing academics': Experiences of change; perceptions of organisational responses; professional and personal impacts; and strategies to support wellbeing. Stress, anxiety and uncertainty of working from home and teaching in a different way were reported. Strategies included setting workday routine, establishing physical boundaries for home-working and regular online contact with colleagues. Conclusions: The ability of nursing, midwifery and, paramedic academic staff to adapt to a sudden increase in workload, change in teaching practices and technology, while being removed from their work environment, and collegial, academic and technological supports is highlighted. It was recognised that these changes will continue post-COVID and that the way academics deliver education is forever altered. Highlights: The pandemic impacted on academic ways of working, workload, and well-being. Online teaching imposed a distance between academic and student. Working from home resulted in a sense of isolation from colleagues. Academics stayed connected, saw the big picture, used experience and exercised. Flexibility and personal contact reassured students.